TEACHERS’ VALUES ATTITUDES AND THEIR DISSEMENTATION IN PEDAGOGICAL ACTIVITIES - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2007)
Values serve as an integrating thread between personal powers and individuals. Thus, their role for educators is of particular importance. Moreover, values become a foundation for competence development. The state of educators’ value principles is revealed through the hierarchy of prioritised values. The following terminal values received highest ratings among the educators in the research: health, happy family, internal harmony, wisdom, active lifestyle; such instrumental values as honesty, responsibility, intelligence, altruism and sophistication were pointed out as the most important. Thus, moral and cognitive (of truths of science) values prevail, including the universally recognised good: health and active lifestyle, which serve as an answer to present challenges and may be neutral from the moral point of view or even acquire a negatyve meaning.The least important terminal values include: pleasures, national security, comfortable life, beauty and the least prioritised instrumental values comprise: obedience, pride, imagination, tidiness and joy. Hence, the values embodying beauty, relations with the nation and faith still give little sense to educators’ lives.Educators lack deep perception of spiritual values. Firstly, such different values in their content as obedience and pride are juxtaposed to each other; secondly, there is a vague understanding of the importance of beauty dimension, especially, when all its manifestations make up the group of least acceptable values and their influence on the individual lose importance; thirdly, only a certain part of values influence educators’ attitude to the actual dissemination of spiritual values, the mission of an educator is narrowly perceived, since it fails to comprise national as well as world history.The research results revealed a devaluation tendency in love as a spiritual value. The key factors influencing the realisation of spiritual values comprise gender and the acquired qualification, whereas working experience is of no relevance.
Keywords: value attitudes; competencies; embodiment of spiritual values